2017
DOI: 10.1002/jcb.26473
|View full text |Cite
|
Sign up to set email alerts
|

Retracted: Effects of apelin on retinal microglial cells in a rat model of oxygen‐induced retinopathy of prematurity

Abstract: This study explores the effects of apelin on retinal microglial cells in rat models of oxygen-induced retinopathy of prematurity (ROP). Totally, 274 rats were selected for establishing oxygen-induced retinopathy (OIR) models, and 92 healthy rats for control group. OIR rats were assigned into OIR, 10 g/L apelin, 10 g/L apelin, and 10 g/L apelin groups. Immunohistochemistry was employed to determine morphology of microglial cells and cell number. CDllb, ionized calcium-binding adapter molecule 1 (IBA-1), TNF-α, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Concurrently, animal studies on retinal endothelial cell lines have demonstrated that apelin-13 has angiogenic activity [18,19]. Many animal studies and a small number of human studies have demonstrated that apelin-13 is associated with the occurrence of ROP [7][8][9]. Thus, systemic apelin-13 and VEGF may be meaningful biomarkers to aid in the diagnosis of ROP [9,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, animal studies on retinal endothelial cell lines have demonstrated that apelin-13 has angiogenic activity [18,19]. Many animal studies and a small number of human studies have demonstrated that apelin-13 is associated with the occurrence of ROP [7][8][9]. Thus, systemic apelin-13 and VEGF may be meaningful biomarkers to aid in the diagnosis of ROP [9,20].…”
Section: Discussionmentioning
confidence: 99%
“…All bioactivity is thought to be in the terminal 13 aa fragment (apelin 13) [6]. In recent years, oxygen-induced neonatal retinopathy mouse experiments have suggested that the expression of apelin-13 can affect vascular density and morphology [7,8]. Furthermore, it may play an important role in pathological retinal neovascularisation and affect the occurrence and development of ROP.…”
Section: Introductionmentioning
confidence: 99%
“…The retinal microglia influence vascular branching density and endothelial cell proliferation [ 21 , 22 ]. They are also implicated in the pathology of diabetic retinopathy and OIR [ 23 , 24 ]. In this study, we investigated the protective effects of GPER activation on hyperoxia-treated primary murine retinal microglia.…”
Section: Introductionmentioning
confidence: 99%